Sosialisasi Kesiapsiagaan Masyarakat dan Arahan Pencegahan Bahaya Kebakaran di Kawasan Permukiman Padat Penduduk (Studi Kasus: Kelurahan Pannampu Kecamatan Tallo Kota Makassar) - Wiwik Wahidah Osman; Mimi Arifin; Arifuddin Akil; Mukti Ali; Sri Aliah Ekawati; Abdul Rachman Rasyid; Yashinta Kumala Dewi Sutopo; Gafar Lakatupa; Jayanti Mandasari; Gianne Aprilia Triasnita (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
One of the problems that often occurs in densely populated settlements is fire disasters which can cause material losses and also cause casualties. Dense settlements in Pannampu Village areas that have a high frequency of fire occurrences. The purpose of this community service activity is to disseminate community preparedness and direct fire prevention in dense residential areas. The partner areas in RW 04 Pannampu Village, Tallo District, Makassar City. Data collection techniques are observation, documentation, and interviews. The data analysis techniques are descriptive qualitative analysis, quantitative and spatial analysis. The data collected is used in the preparation of directives in the form of socialization and discussions with the community, community leaders and the academic community. The results of service activities produce 5 factors that affect the level of fire vulnerability in a settlement, namely building density, building materials, road width, affordability of water sources and fire stations. There are also 6 scenarios of evacuation routes from 4 points of vulnerable locations to Temporary Evacuation Places (TES), and 4 fire extinguishers that can be used as a basis for consideration in choosing the right evacuation route. Adaptive and curative efforts are in the form of developing disaster response groups as preparation management in dealing with fire disasters. The socialization results showed a significant level of change by the community where the level of interest in community participation and understanding of the concept of handling fire hazards increased. Before the activity was carried out, the level of understanding of the concept of fire disaster management/mitigation was 35.5%, but after the socialization activity was carried out it increased to 75.8%. Thus there is an increase in public understanding of 40.3%. This shows that the output of the socialization of community preparedness for fire disasters was successful.